Television style - Butler, Jeremy G., 1954- (Routledge, 2010)
"Style matters. Television relies on style - setting, lighting, videography, editing, and so on - to set moods, hail viewers, construct meanings, build narratives, sell products, and shape information. Yet, to date, style has been the most understudied aspect of the medium. In this book, Jeremy G. Butler examines the meanings behind television's stylistic conventions." "Television Style dissects how style signifies and what significance it has had in specific television contexts. Using hundreds of frame captures from television programs, Television Style dares to look closely at television. Miami Vice, ER, soap operas, sitcoms, and commercials, among other prototypical television texts, are deconstructed in an attempt to understand how style functions in television. Television Style also assays the state of style during an era of media convergence and the ostensible demise of network television." --Book Jacket.